Neoplasms with eccrine differentiation - Soyer, H... Peter (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1997)
In the present article emphasis is given on four entities with eccrine differentiation that may pose problems in interpretation and classification: adenoid-cystic hyperplasia of eccrine glands, eccrine syringofibroadenomatosis, malignant giant eccrine acrosporoma and eccrine epithelioma.
Keywords: Acrospiroma, eccrine; Carcinoma; Giant cell tumors; Hyperplasia; Sweat gland neoplasms; Syringoma